A Cross-Platform, High Performance Shared Storage System - Nordstrand, Rickard (My University, 2009)
Advancements in information technology pushes the requirements of networks and storage solutions to new levels. The digital media industry is one particular area where the increased performance demands conflicts with the requirements of multi-user, cross-platform systems. While the concept of Storage Area Networks (SAN) sets new records on data throughput speeds, the interopability between Windows and OS X systems offered by Network Attached Storage (NAS) is lost. SweDisk is a startup company that works closely with the digital media industry to develop new storage solutions to fit their constantly higher demands. A new prototype system is designed, implemented and deployed at customer sites as distributed systems and user-space filesystems play key roles when the supercomputing concepts of clustering and scalable storage are brought to the world of digital media production. ____________________________________________________________ //Sammanfattning // Stora framsteg inom informationstekniken ställer nya krav på nätverk och lagringslösningar. Den digitala mediabranschen är ett av områdena där de ökade prestandakraven kolliderar med krave på fleranvändarstöd och plattformsoberoende. Medan SAN-lösningar slår nya rekord i överföringshastighet går man miste om det så givna plattformsoberoendet i NAS-systemen. SweDisk är ett ungt företag som med hjälp av ett nära samarbete med den digitala mediabranschen utvecklar nya lagringssystem för att uppfylla de allt högre kraven. Distribuerade system och user-space-filsystem spelar huvudrollerna när superdator-koncepten kluster och skalbar lagring introduceras i den digitala mediabranschen när ett nytt prototypsystem tas fram och driftsätts hos kund.
Keywords: Datorteknik; Computer Engineering